Pogledi na poklic športnega pedagoga in stanovsko organizacijo - Berčič, Herman (Šport (Ljubljana), 2013)
This year's (35th) anniversary of the Slovenian Association of Sport Teachers' Societies is a good opportunity to pay some consideration to the profession of sport teacher, the state of affairs in the professional organisation, its organisation, the contents of the activities as well as the relations and co-operation among its members. According to the analysed results, the current situation is not gratifying. There are several reasons for this. The number of active members should be increased, the relations and co-operation between the members enhanced, while the activities should aim to achieve the better recognisability of the professional organisation and improve its reputation in professional circles and the broader public. Co-operation with the parent faculty should also improve. It is possible to achieve this with some fresh ideas and novelties in terms of organisation and contents. The above would undoubtedly help broaden the knowledge of new generations and generate new findings as well as improve the attitude to the sport profession and science, along with the attitude to the Faculty of Sport.
Keywords: connections; co-operation; education; Faculty of Sport; Fakulteta za šport; pogledi; povezovanje; professional organisation; sodelovanje; sport; sport teachers; stanovska organizacija; šport; športni pedagogi; views